Socio Cultural Practices and the Level of Implementation of Policies for Universal Primary Education: The Case of the Mbororo Community of the North West Region of Cameroon - Kimeng Liberty Song; Nforbi Sharlotte Lem (Researchparks Publishing, 2022)
The study was to find out the extent to which cultural practices amongst Mbororos affects the implementation of policies for universal primary education in the Mbororo community of the North West Region of Cameroon”. This study was guided by the Bourdieu’s theory of cultural capital. The target population was 3500, and sample was 308 respondents, Snow ball, purposive and convenience sampling technique was used, questionnaire and interview guide was used to collect data, and data were analyzed using thematic content analysis, frequencies, proportions and chi-square. The results indicated that: There is a significant influence of culture, religion on the implementation of UPE. lack of finance, family support, early marriages, inadequate school facilities, nomadic life style, poor infrastructure, cultural values like drum beating, isolated settlement, limited Islamic schools, high illiteracy, are some of the factors that hinder the implementation of UPE in the Mbororo Community of the North-West region of Cameroon. The study recommends that Ardors or chiefs should be sensitized to disseminate educational talks to their local communities. The content of the curriculum should be relevant to Mbororo children, should also responds to cultural diversity. Parents and the entire community should be schooled on the importance of education to both the child and the community in general. Suggestions were made for this study to be replicated in the North -West Region of Cameroon using a larger sample.